Gambaran Kebiasaan Makan Makanan Beresiko Penyakit Jantung Koroner Pada Masyarakat Etnis Minahasa di Lingkungan 2 Kelurahan Bahu Kecamatan Malalayang Kota Manado - Bororing, Felastri Delais; Kandou, Grace D.; Rombot, Dina V. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Coronary heart disease (CHD) is one of degenerative diseases which is the biggest cause of death and also main causeof death in indonesia’s population aged over 40 years old. This disease is generally caused by unhealthy behaviour orlifestyle. The community of ethnic Minahasa has custom party followed by junket or eating Minahasan dish which arelargely derived from animal fat (pork). This study aimed to describe the overview of eating habit which was the typeof food and the frequency of eating risky food that can cause CHD and also the overview of past incidence of CHD oncommunity of ethnic Minahasa in Environment 2 Bahu Village District Malalayang Manado City. This is a descriptivestudy with method used was by questionnaire and followed by interview. The sample in this study was 43 heads ofthe family or housewives ethnic Minahasa with certain criteria. The result showed that among 25 types of food thatcould potentially lead to CHD based on frequently consumed meal (≥2 times per month), there were 10 types of frequentlyconsumed meal which were sayur kangkung tumis (76.7%), babi garo rica (37.2%), brenebon babi (37.2%),sayur pait ba’ (30.2%), sate babi (23.3%), babi tore (23.3%), babi kecap (20.9%), babi bakar (16.3%), babi leylem(16.3%) and rw/anjing (16.3%). There were incidence of past CHD (4.7%) who had the disease for more than 1 year,history of CHD in family (20.9%) and history of diseases that could potentially lead to CHD which were diabetes mellitus(18.6%), hypertension (53.5%), hyperuricemia (27.9%) and dyslipidemia (18.6%). Conclusions of this study thatthere were 10 types of frequently consumed food based on frequently consumption (≥2 times per month) which weresayur kangkung tumis, babi garo rica, brenebon babi, sayur pait ba’, sate babi, babi tore, babi kecap, babi bakar, babileylem, dan rw/anjing. There were history of CHD for over 1 year found among 43 respondents.Keywords: Eating habit, coronary heard disease